Large solubility of lithium carboxylates reaching high rates of 6Li incorporation in polystyrene-based plastic scintillators for fast/thermal neutron and gamma ray detection. (18th June 2019) - Frangville, Camille; Hamel, Matthieu; Bertrand, Guillaume H. V.; Montbarbon, Eva; Grabowski, Amélie; Lynde, Clément
Abstract : 6 Li-Doped plastic scintillators (PSs) have been optimized as radioluminescent sensors for detection of fast/thermal neutrons and gamma rays for several purposes such as homeland security. Abstract : 6 Li-Doped plastic scintillators (PSs) have been optimized as radioluminescent sensors for detection of fast/thermal neutrons and gamma rays for several purposes such as homeland security. Among 16 low molecular weight (C < 8) lithium carboxylates, Liα-valerate (LiαVal) exhibits high potential for loading (up to 50 wt%) in clear PSs composed of polystyrene and standard fluors (20 wt% PPO, 0.03 wt% POPOP). A methodical study of PS composition illustrates that the Li carboxylates and methacrylic acid comonomers impact the scintillation yields (from 4410 to 7790 ph per MeV) and n thermal / n fast /gamma discrimination performances with significant figures of merit (from 0.23 to 1.45 above 180 keVee).